2008
DOI: 10.1007/s00264-008-0679-8
|View full text |Cite
|
Sign up to set email alerts
|

Osteolysis with a cementless second generation metal-on-metal cup in total hip replacement

Abstract: This study examined the long-term results of a metal-on-metal total hip replacement with a Metasul-lined cup. Twenty-nine total hip arthroplasties were performed in 27 young patients (mean age 49 years). Twenty-two patients (23 hips) were available for clinical and radiographic analysis after a mean duration of 99 months. Mean preoperative Harris hip score of 60 improved to 93 at most recent follow-up. One patient required revision of his cup for periacetabular osteolysis. Radiographic analysis showed osteolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 30 publications
1
18
2
2
Order By: Relevance
“…However, all patients with osteolysis in our series had normal blood metal ion levels; and pseudotumors have been found common in well-functioning low-wearing MoM hips with no osteolysis [22,33]. In addition, in ARMD, one would expect the osteolysis to affect both the acetabular and the femoral neck bone, a finding noted in previous papers on osteolysis associated with MoM hips [10,28]. In our series the osteolysis only affected the femoral neck, except in one case (the most severe case) in which it did affect the acetabular bone (Fig.…”
Section: Study Limitationssupporting
confidence: 55%
See 1 more Smart Citation
“…However, all patients with osteolysis in our series had normal blood metal ion levels; and pseudotumors have been found common in well-functioning low-wearing MoM hips with no osteolysis [22,33]. In addition, in ARMD, one would expect the osteolysis to affect both the acetabular and the femoral neck bone, a finding noted in previous papers on osteolysis associated with MoM hips [10,28]. In our series the osteolysis only affected the femoral neck, except in one case (the most severe case) in which it did affect the acetabular bone (Fig.…”
Section: Study Limitationssupporting
confidence: 55%
“…Patients' median OHS (using the 48-point OHS) improved from 26 (range, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] preoperatively to 46 (range, [35][36][37][38][39][40][41][42][43][44][45][46][47][48], and UCLA score improved from 5 (range, 2-8) to 8 (range, 4-10) at latest review (paired t-test p \ 0.001 for both). There was no difference in median [35][36][37][38][39][40][41][42][43][44][45][46][47][48] or in the median postoperative UCLA scores between males (8; range, 5-10) and females (8; range, 4-10) (Mann-Whitney U p = 0.293 and p = 0.115, respectively).…”
Section: Survivorship and Hip Scoresmentioning
confidence: 99%
“…However, ALVAL has also been described in periprosthetic tissues surrounding well-fixed implants with a contemporary MOM-bearing couple [17]. Conversely, high rates of periacetabular osteolysis have been reported in a recent series of MOM hip replacements, with no argument in favour of tissue reaction to metallic debris [7]. In contrast to with previous studies [10,27], other authors failed to correlate the presence of lymphocyte aggregates and the appearance of osteolysis [17].…”
Section: Discussioncontrasting
confidence: 38%
“…Although initial reports were satisfactory [5,14,22,28,29], subsequent research demonstrated unacceptable early failure rates of monoblock MoM THAs, resulting in a substantial revision burden [2-4, 6, 7, 10, 12, 13, 15, 18, 19, 21, 24, 25, 27, 30, 32, 33, 36]. These revisions can be complicated by extensive soft tissue and bony defects, persistence of adverse local tissue reaction as well as problems associated with the general need to reduce the head size at the time of revision, perhaps increasing the likelihood of dislocation [1,3,7,10,13,18,19,23,25,31,33]. Previous studies reporting on the early complications after these revisions are limited and generally of small number [3,10,31,35].…”
Section: Introductionmentioning
confidence: 99%